Uprawnienia interwenienta w postępowaniu karnym skarbowym - Zajcew-Szwaj, Mirosława (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2019)
The article presents the rights of the intervener in Fiscal Penal Law. The institution of intervention is a specific regulation that has no counterpart in common criminal proceedings. The article describes the concept of intervention, deadlines and forms of its notification and the rights of the intervener, whose procedural interest is the prevention of the forfeiture of objects to which he is entitled. It is indicated that the current provisions should be clarified.
Keywords: forfeiture; the institution of intervention; protection of property; the Fiscal Penal Code